Fotografování terénu z letounu - Skočdopole, Jan (Vysoké učení technické v Brně. Fakulta informačních technologií, 2018)
Práce se zabývá fotografováním terénu z letounu. Předmětem řešení jsou fáze plánování a~přípravy letu, navigace, pořizování snímků a ukládání telemetrie. Pro tyto účely je využita externí kamera umístěná pod trupem letounu a tablet s aplikací umístěný uvnitř kabiny.

This thesis deals with terrain photography from an aircraft. Subject of solution includes phases of planning and preparation of flight, navigation, taking images and telemetry recording. For this purpose remote camera placed under planes hull and tablet with application placed in the cockpit are used.
Terrain Photographing from an Aircraft
Keywords: fotografování terénu z letounu; fotogrammetrie; navigace; GPS; Android; Java; terrain photography from an aircraft; photogrammetry; navigation; GPS; Android; Java